FIRST HIGHER EDUCATIONAL UNIVERSITY OF JIZZAKH - Mahammatov Akram (Web of Journals Publishing, 2024)
This article talks about the Jizzakh State Pedagogical Institute, which was founded in 1974 in the Jizzakh oasis, how the university was founded, the material and technical base, research work and the educational process. The article also talks about the general activities of the university over half a century.
Keywords: Jizzakh oasis, institute, university, rector, vice-rector, faculty, research work, scientific potential, material and technical base, educational process, professor, associate professor, student, team, scientific school.